Defects and Damage in Composite Materials and Structures - Heslehurst, Rikard Benton (CRC Press, Taylor & Francis Group, 2014)
The advantages of composite materials include a high specific strength and stiffness, formability, and a comparative resistance to fatigue cracking and corrosion. However, not forsaking these advantages, composite materials are prone to a wide range of defects and damage that can significantly reduce the residual strength and stiffness of a structure or result in unfavorable load paths. Emphasizing defect identification and restitution, Defects and Damage in Composite Materials and Structures explains how defects and damage in composite materials and structures impact composite component performance. Providing ready access to an extensive, descriptive list of defects and damage types, this must-have reference: Examines defect criticality in composite structures Recommends repair actions to restore structural integrity Discusses failure modes and mechanisms of composites due to defects Reviews NDI processes for finding and identifying defects in composite materials Relating defect detection methods to defect type, the author merges his experience in the field of in-service activities for composite airframe maintenance and repair with indispensable reports and articles on defects and damage in advanced composite materials from the last 50 years.